Analysis of the Physical Demand of Rugby 7s Athletes - Dito Dwi Cahyo; Herdiansyah Agus; Patriana Nurmansyah Awwaludin; Bayu Santoso; Hadiat Aliansyah (Physical Activity Journal (PAJU), 2025)
This study aims to analyze the physical condition of Rugby 7s athletes, focusing on aerobic endurance, speed, and agility. A total of 12 male provincial-level Rugby 7s athletes who participated in the 2024 XXI National Sports Week (PON) in Aceh–North Sumatra were involved in the study. Aerobic endurance was assessed using the 12-minute run test (Cooper Test), speed was measured through 10-meter, 30-meter, and 30-meter flying start sprint tests, while agility was evaluated using the standardized T-Test. The results showed variations in physical performance among the athletes, reflecting individual fitness levels across the three components tested. These findings provide a comprehensive overview of the physical condition profiles of Rugby 7s athletes and emphasize the importance of aerobic endurance, speed, and agility in supporting game performance. This study contributes valuable benchmark data for evaluating and designing more specific, structured, and effective physical training programs. Coaches and sports practitioners can utilize these results to develop more targeted training strategies, aiming to enhance the competitive performance and achievements of Rugby 7s athletes.